Model Pembelajaran Laboratory Training dan Implementasinya dalam Pembelajaran Pendidikan Agama Islam - Ulfah Nur Fauziah; Syahidin (Gunung Djati Conference Series, 2022)
The issuance of the Regulation of the Minister of Religion of the Republic of Indonesia regarding national standards in the implementation of Islamic religious education in schools requires educators to determine the appropriate learning model in an effort to balance the demands for the progress of facilities and infrastructure in it. So this research is intended to examine the laboratory training learning model and its implementation towards Islamic religious education learning which is expected to be an option in answering these problems. The research was conducted with a qualitative approach and using library research. The results of this study indicate that the laboratory training learning model is a group learning model in which each group is faced directly with a situation, phenomenon or problem, so that students can immediately learn and solve it. The purpose of this model can be seen from three dimensions, namely: intrapersonal, interpersonal, group dynamics and self-direction. Therefore, this model has the potential to be implemented in Islamic religious education as one of the subjects that not only emphasizes the cognitive aspect and this model is expected to be able to balance the demands for the advancement of Islamic religious education facilities and infrastructure in schools and overcome the problems of learning Islamic religious education which seem boring and monotonous.